2023
DOI: 10.1097/md.0000000000033726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the application of 18F-FDG and 68Ga-DOTATATE PET/CT in neuroendocrine tumors: A retrospective study

Abstract: The present study aimed to compare the efficacy of 68 Ga-DOTATATE PET/CT and 18 F-FDG PET/CT imaging in the diagnosis, staging, and prognosis evaluation of neuroendocrine tumors (NET). A total of 55 patients (43 were initially evaluated, 12 were evaluated after treatment) who underwent fluorine-18 labeled fluorodeoxyglucose ( 18 F-FDG) and 68 Ga DOTATE PET/CT examinations were reviewed retrospectively, and the pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The main advantage of nuclear medicine is that different radiopharmaceuticals can be synthesized for targeted imaging based on receptors expressed in the lesion. 18 F-FDG PET/CT, a common functional imaging technique, has been widely used in the localization, differential diagnosis, staging and post-treatment response assessment of a variety of primary tumors; however, it has shown limited value in the diagnosis and differential diagnosis of neuroendocrine tumors, including insulinoma ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of nuclear medicine is that different radiopharmaceuticals can be synthesized for targeted imaging based on receptors expressed in the lesion. 18 F-FDG PET/CT, a common functional imaging technique, has been widely used in the localization, differential diagnosis, staging and post-treatment response assessment of a variety of primary tumors; however, it has shown limited value in the diagnosis and differential diagnosis of neuroendocrine tumors, including insulinoma ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…New imaging techniques in nuclear medicine, including PET/CT imaging with 68 Ga-somatostatin receptors, such as 68 Ga-DOTATATE, and 68 Ga-glucagon-like peptide-1 (GLP-1) receptor analogs, such as 68 Ga-DOTA-exendin-4, can facilitate the localization and diagnosis of insulinoma to distinguish it from other tumors such as pancreatic cancer and pancreatic cystadenoma ( 7 , 17 , 18 ). Due to the high expression of somatostatin receptors, insulinomas show significant radioactivity uptake on 68 Ga-somatostatin receptor and 68 Ga-GLP-1 receptor analog PET/CT imaging ( 7 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT. The production of 18 F-FDG and PET/CT (Biograph mCT, Siemens, Germany) scanning parameters were conducted based on our previously published literature (7).…”
Section: Image Acquisitionmentioning
confidence: 99%
“…However, its diagnostic value for cystic lesions is limited. Numerous studies have demonstrated that Ga68 SSA-PET([ 68 Ga]Ga-DOTANOC, [ 68 Ga]Ga-DOTATOC, [ 68 Ga]Ga-DOTATATE) imaging offers higher diagnostic accuracy for NETs (2)(3)(4)(5). While 68Ga labeling has the advantage of eluting isotopes from a generator, fluorine labeling offers benefits like longer half-life, improved spatial resolution, higher production yield, and consistent advantages in imaging and logistics.…”
Section: Introductionmentioning
confidence: 99%